Degradability, Phytotoxicity, and Life Cycle Assessment of Chestnut Waste Biocomposites - Simão B. Silva; Samara Rodrigues; Elena Surra; Elsa Vieira; Cristina Delerue-Matos; Olga M. Freitas; Valentina F. Domingues (Environmental Processes, 2026)

Risks of exceeding health-based guidance values for toxic metals and metalloids through seaweed and halophyte consumption - Elsa T. Rodrigues; Leonel Pereira; Eduarda Pereira; Miguel A. Pardal (Food Control, 2025)

Temporal dynamics of class 1 and class 3 integron pools in treated wastewater - Rafael D.S. Tavares; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Water Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Plastisphere in a low-pollution mountain river: Influence of microplastics on survival of pathogenic bacteria - Isabel Silva; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Chemosphere, 2024)

Portuguese macroalgae and halophytes for human consumption: Minimal risk of norovirus and Salmonella infection - Joana M. Oliveira; Miguel A. Pardal; Leonel Pereira; Ana M. Matos; Elsa T. Rodrigues (Food Control, 2024)

Integron-associated genes are reliable indicators of antibiotic resistance in wastewater despite treatment- and seasonality-driven fluctuations - Rafael D.S. Tavares; Cátia Fidalgo; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Water Research, 2024)

Effect of photostimulation through red LED light radiation on natural fermentation of table olives: An innovative case study with Negrinha the Freixo variety - Fátima Martins; Elsa Ramalhosa; Nuno Rodrigues; José Alberto Pereira; Paula Baptista; Maria Filomena F. Barreiro; Pedro J.L. Crugeira (Journal of Photochemistry and Photobiology B: Biology, 2024)

Effect of the cleaning and disinfection methods on the hygienic conditions of fermentation tanks of table olives (Olea europaea L.) Negrinha de Freixo cultivar - Fátima Martins; Nuno Rodrigues; José Alberto Pereira; Paula Baptista; Elsa Ramalhosa (Food Microbiology, 2024)

Altered expression of Sialyl Lewis X in experimental models of Parkinson’s disease - Maria João Nunes; Andreia Neves Carvalho; Alexandra I. Rosa; Paula A. Videira; Maria João Gama; Elsa Rodrigues; Margarida Castro-Caldas (Journal of Molecular Medicine, 2024)
The mechanisms underlying neurodegeneration in Parkinson’s disease (PD) are still not fully understood. Glycosylation is an important post-translational modification that affects protein function, cell-cell contacts and inflammation and can be modified in pathologic conditions. Although the involvement of aberrant glycosylation has been proposed for PD, the knowledge of the diversity of glycans and their role in PD is still minimal. Sialyl Lewis X (sLeX) is a sialylated and fucosylated tetrasaccharide with essential roles in cell-to-cell recognition processes. Pathological conditions and pro-inflammatory mediators can up-regulate sLeX expression on cell surfaces, which has important consequences in intracellular signalling and immune function. Here, we investigated the expression of this glycan using in vivo and in vitro models of PD. We show the activation of deleterious glycation-related pathways in mouse striatum upon treatment with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a toxin-based model of PD. Importantly, our results show that MPTP triggers the presentation of more proteins decorated with sLeX in mouse cortex and striatum in a time-dependent manner, as well as increased mRNA expression of its rate-limiting enzyme fucosyltransferase 7. sLeX is expressed in neurons, including dopaminergic neurons, and microglia. Although the underlying mechanism that drives increased sLeX epitopes, the nature of the protein scaffolds and their functional importance in PD remain unknown, our data suggest for the first time that sLeX in the brain may have a role in neuronal signalling and immunomodulation in pathological conditions. Key messages MPTP triggers the presentation of proteins decorated with sLeX in mouse brain. MPTP triggers the expression of sLeX rate-limiting enzyme FUT 7 in striatum. sLeX is expressed in neurons, including dopaminergic neurons, and microglia. sLeX in the brain may have a role in neuronal signalling and immunomodulation.

Investigation of landslide hazard areas in the municipality of Cunha (Brazil) and climate projections from 2024 to 2040 - Irving Rodrigues de Souza; Débora Luisa Silva Teixeira; Marcelo Barbio Rosa; Luiz Tadeu da Silva; Jean Pierre Henry Balbaud Ometto; Danúbia Caporusso Bargos; Cristina Andrade; Elsa Paula Figueira Ferreira Morgado de Sampaio; Paulo Valladares Soares; Thiago Bazzan (Urban Climate, 2023)

The H9c2(2-1) cell-based sulforhodamine B assay is a non-animal alternative to evaluate municipal wastewater quality over time - Elsa T. Rodrigues; Eduarda Pereira; Paulo J. Oliveira; Miguel A. Pardal (Environmental Monitoring and Assessment, 2023)
The present study validates the potential of the in vitro H9c2(2-1) cell-based sulforhodamine B (SRB) assay to evaluate the temporal variability of wastewater quality. The impact of effluent disposal on water quality and the efficiency of the wastewater treatment process were also assessed. To correlate standard analytical method results with in vitro results, a total of 16 physicochemical parameters, such as nutrients, pH, chemical oxygen demand, total suspended solids and metals, were determined in both raw and treated wastewater samples. Results revealed that the H9c2(2-1) cell-based SRB assay has an enormous potential to evaluate municipal wastewater quality over time and to discriminate influent and effluent toxic characteristics, as well as for water quality monitoring and surveillance of the efficacy of treatment processes. Finally, the gathered results alerted to the impact of phosphates in a biological system, leading us to recommend the selection of this parameter as a potential environmental health indicator.

Microplastics accumulate priority antibiotic-resistant pathogens: Evidence from the riverine plastisphere - Isabel Silva; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Environmental Pollution, 2023)

Improving the control of pharmaceutical compounds in activated sludge wastewater treatment plants: Key operating conditions and monitoring parameters - Catarina Silva; Cristina M.M. Almeida; João A. Rodrigues; Sofia Silva; Maria do Rosário Coelho; António Martins; Rita Lourinho; Eugénia Cardoso; Vítor Vale Cardoso; Maria João Benoliel; Elsa Mesquita; Rita Ribeiro; et al. (Journal of Water Process Engineering, 2023)

How Can Geoscience Communication Foster Public Engagement with Geoconservation? - Joana Rodrigues; Elsa Costa e Silva; Diamantino Insua Pereira (Geoheritage, 2023)
Geoscience and geodiversity, two sides of the same coin, deal with very poor social visibility and recognition. Ensuring the protection of geodiversity is not only in the geoscientists’ hands and all of society needs to be involved. Therefore, public engagement with geodiversity demands new solutions and a change of paradigm in geoscience communication. Most of the science communication activities undertaken by geoscientists, even when they use modern approaches and technologies, are mainly designed based on empirical experience, laid on didactical approaches and assuming the public’s knowledge deficit. In order to engage the society with geodiversity, it is not enough to focus on scientific literacy and deficit models in which lack of knowledge is considered to be the main obstacle between science and society. It is fundamental to establish a commitment between society and science based on dialogue where lay public is not seen anymore as a single entity with a knowledge deficit. Non-experts must become also protagonists in scientific decisions with social impact and integrate their knowledge and concerns in public participation and decision-making. Engagement with geoscience and geodiversity would benefit from more effective and targeted communication strategies, with different approaches to engage with communities, local stakeholders, media, students and teachers, scientific community, tourists, politicians or policy-makers, and groups with different concerns and distinct relations with science. In the last 20 years, science communication research has made many relevant contributions in order to promote more participatory processes with which society is asked to engage. Regarding geoscience communication as a discipline, it is a very recent Earth science branch that also incorporates social science, behavioral science, and science communication, but still lacks a clear and formal definition. This study provides a comprehensive review of the literature in order to develop a conceptual framework for geoscience communication research, identifying the main challenges and opportunities.

Are mercury levels in fishery products appropriate to ensure low risk to high fish-consumption populations? - Elsa T. Rodrigues; João P. Coelho; Eduarda Pereira; Miguel A. Pardal (Marine Pollution Bulletin, 2023)

Evaluating general combining ability for agro-morphological traits in tetraploid bahiagrass - Florencia Marcón; Elsa A. Brugnoli; José A. Rodrigues Nunes; Valeria A. Gutierrez; Eric J. Martínez; Carlos A. Acuña (Euphytica, 2021)

Determination of intestinal absorption of the paralytic shellfish toxin GTX-5 using the Caco-2 human cell model - Elsa T. Rodrigues; Susana F. Nascimento; Cristiana L. Pires; Lia P. Godinho; Catarina Churro; Maria João Moreno; Miguel A. Pardal (Environmental Science and Pollution Research, 2021)

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Changes in salivary protein composition of lambs supplemented with aerial parts and condensed tannins: extract from Cistus ladanifer L.—a preliminary study - Elsa Lamy; Lénia Rodrigues; Olinda Guerreiro; David Soldado; Alexandra Francisco; Monica Lima; Fernando Capela e Silva; Orlando Lopes; José Santos-Silva; Eliana Jerónimo (Agroforestry Systems, 2020)

Assessment and mitigation of seismic risk at the urban scale: an application to the historic city center of Leiria, Portugal - Anna Blyth; Beatrice Di Napoli; Francesco Parisse; Zahir Namourah; Elsa Anglade; Anna-Maria Giatreli; Hugo Rodrigues; Tiago Miguel Ferreira (Bulletin of Earthquake Engineering, 2020)

Cell-based assays as an alternative for the study of aquatic toxicity of pharmaceuticals - Elsa T. Rodrigues; Ana T. Varela; Miguel A. Pardal; Vilma A. Sardão (Environmental Science and Pollution Research, 2020)

The environmental condition of an estuarine ecosystem disturbed by pesticides - Elsa T. Rodrigues; Maria Fátima Alpendurada; Ana Guimarães; Romeu Avó; Bárbara Ferreira; Miguel A. Pardal (Environmental Science and Pollution Research, 2019)

Tauroursodeoxycholic Acid Improves Motor Symptoms in a Mouse Model of Parkinson’s Disease - Alexandra Isabel Rosa; Sara Duarte-Silva; Anabela Silva-Fernandes; Maria João Nunes; Andreia Neves Carvalho; Elsa Rodrigues; Maria João Gama; Cecília Maria Pereira Rodrigues; Patrícia Maciel; Margarida Castro-Caldas (Molecular Neurobiology, 2018)

Erratum to: Tauroursodeoxycholic Acid Protects Against Mitochondrial Dysfunction and Cell Death via Mitophagy in Human Neuroblastoma Cells - Inês Fonseca; Gisela Gordino; Sara Moreira; Maria João Nunes; Carla Azevedo; Maria João Gama; Elsa Rodrigues; Cecília Maria Pereira Rodrigues; Margarida Castro-Caldas (Molecular Neurobiology, 2017)

Tauroursodeoxycholic Acid Protects Against Mitochondrial Dysfunction and Cell Death via Mitophagy in Human Neuroblastoma Cells - Inês Fonseca; Gisela Gordino; Sara Moreira; Maria João Nunes; Carla Azevedo; Maria João Gama; Elsa Rodrigues; Cecília Maria Pereira Rodrigues; Margarida Castro-Caldas (Molecular Neurobiology, 2017)

Bacterial host and reporter gene optimization for genetically encoded whole cell biosensors - Catherine Brutesco; Sandra Prévéral; Camille Escoffier; Elodie C. T. Descamps; Elsa Prudent; Julien Cayron; Louis Dumas; Manon Ricquebourg; Géraldine Adryanczyk-Perrier; Arjan de Groot; Daniel Garcia; Agnès Rodrigue; et al. (Environmental Science and Pollution Research, 2017)

Pushing the limits of nickel detection to nanomolar range using a set of engineered bioluminescent Escherichia coli - Julien Cayron; Elsa Prudent; Camille Escoffier; Erwan Gueguen; Marie-Andrée Mandrand-Berthelot; David Pignol; Daniel Garcia; Agnès Rodrigue (Environmental Science and Pollution Research, 2017)

Changes in the salivary protein profile of morbidly obese women either previously subjected to bariatric surgery or not - Elsa Lamy; Carla Simões; Lénia Rodrigues; Ana Rodrigues Costa; Rui Vitorino; Francisco Amado; Célia Antunes; Isabel do Carmo (Journal of Physiology and Biochemistry, 2015)

Cholesterol 24S-Hydroxylase Overexpression Inhibits the Liver X Receptor (LXR) Pathway by Activating Small Guanosine Triphosphate-Binding Proteins (sGTPases) in Neuronal Cells - Miguel Moutinho; Maria João Nunes; Anita Q. Gomes; Maria João Gama; Angel Cedazo-Minguez; Cecília M. P. Rodrigues; Ingemar Björkhem; Elsa Rodrigues (Molecular Neurobiology, 2015)

Primary Productivity Temporal Fluctuations in a Nutrient-Rich Estuary due to Climate-Driven Events - Elsa T. Rodrigues; Miguel Â. Pardal (Estuaries and Coasts, 2015)

Ubiquitin–Proteasome System Impairment and MPTP-Induced Oxidative Stress in the Brain of C57BL/6 Wild-type and GSTP Knockout Mice - Andreia Neves Carvalho; Carla Marques; Elsa Rodrigues; Colin J. Henderson; C. Roland Wolf; Paulo Pereira; Maria João Gama (Molecular Neurobiology, 2013)

Glutathione S-Transferase pi Mediates MPTP-Induced c-Jun N-Terminal Kinase Activation in the Nigrostriatal Pathway - Margarida Castro-Caldas; Andreia Neves Carvalho; Elsa Rodrigues; Colin Henderson; C. Roland Wolf; Maria João Gama (Molecular Neurobiology, 2012)

Dietary restriction improves systemic and muscular oxidative stress in type 2 diabetic Goto–Kakizaki rats - Lisa Rodrigues; Joana Crisóstomo; Paulo Matafome; Teresa Louro; Elsa Nunes; Raquel Seiça (Journal of Physiology and Biochemistry, 2011)

GSTpi Expression in MPTP-Induced Dopaminergic Neurodegeneration of C57BL/6 Mouse Midbrain and Striatum - Margarida Castro-Caldas; Andreia Neves Carvalho; Isabel Peixeiro; Elsa Rodrigues; Maria Celeste Lechner; Maria João Gama (Journal of Molecular Neuroscience, 2009)

Pharmacological Modulation of Epithelial Mesenchymal Transition Caused by Angiotensin II. Role of ROCK and MAPK Pathways - Raquel Rodrigues-Díez; Gisselle Carvajal-González; Elsa Sánchez-López; Juan Rodríguez-Vita; Raúl Rodrigues Díez; Rafael Selgas; Alberto Ortiz; Jesús Egido; Sergio Mezzano; Marta Ruiz-Ortega (Pharmaceutical Research, 2008)

Degradation of Leaf Litter Phenolics by Aquatic and Terrestrial Isopods - Martin Zimmer; Ricardo Oliveira; Elsa Rodrigues; Manuel A. S. Graça (Journal of Chemical Ecology, 2005)